EVALUATION OF THE APPLICABILITY OF INDONESIAN CRIMINAL PROCEDURE CODE - ROYANI, ACHMAD; ISNAINI, ENIK; WINARNO, JATMIKO (Jurnal Independent, 2022)
AbstractionEven though it was promulgated more than 40 years ago, the Criminal Procedure Code(KUHAP) is still the main reference for the operationalization of the criminal justice systemin Indonesia. During the same period, the practice of criminal procedural law developed sorapidly and slowly revealed imperfections in the basic building and design of the criminaljustice system regulated in the Criminal Procedure Code. The Criminal Procedure Codeaudit was prepared with the aim of providing a complete portrait of the problematicIndonesian criminal procedural law based on factual evidence in judicial practice. In the firstpart, the context of the analysis is aimed at regulatory gaps and deviations shown at theimplementation level. The basic assumptions built regarding the integrity and integration ofthe Indonesian criminal justice system are tested by basing them on empirical research andobservation, including an in-depth review of court decisions. This research also records thecurrent dynamics of criminal procedural law which are translated, formed, and reinterpretedby the courts, including through cases tried by the Supreme Court and the ConstitutionalCourt.